Konservatisme Akuntansi Syariah pada Perusahaan Properti dan Real Estate yang Terdaftar pada ISSI Periode 2021-2022 - Harkaneri; Elisa Novianty; Hidayati Nasrah; Ghali Dwi Diharja (Yayasan Almanar Pujud, 2025)
This research is a quantitative study that aims to investigate the influence of institutional ownership, company size, financial distress, and leverage on sharia accounting conservatism in property and real estate companies listed on the ISSI for the 2021-2022 period. The study's sample consists of 51 companies, selected using a purposive sampling method. Secondary data for this research was obtained from the annual reports of these companies. Data analysis was conducted using panel data regression, which included descriptive statistical analysis, classical assumption testing, panel data regression model selection, and hypothesis testing. The findings from the panel data regression analysis indicate that financial distress positively affects sharia accounting conservatism, while leverage negatively impacts sharia accounting conservatism. Conversely, institutional ownership and company size were found to have no significant effect on sharia accounting conservatism. This study contributes to the existing literature by providing insights into the factors influencing sharia accounting conservatism in the property and real estate sector. These findings can help stakeholders, including investors, regulators, and company management, to better understand the dynamics of sharia accounting practices and make informed decisions.